A specific energy-based size reduction model for batch grinding ball mill. (January 2015) - Shi, Fengnian; Xie, Weiguo
Highlights: A specific energy-based size reduction model has been developed for ball mill. Ore-specific and size-dependent breakage function is incorporated in the model. A fine-particle breakage characteriser (JKFBC) used for breakage characterisation. The model shows improved predictability for ball mill batch grinding products. Abstract: A particle size reduction model has been developed as the first component of an upgraded ball mill model. The model is based on a specific energy-size reduction function, which calculates the particle breakage index, t 10, according to the size-specific energy, and then calculates the full product size distribution using the t 10 – tn relationships and the mass-size balance approach. The model employs an ore-specific and size-dependent breakage function, whose parameters are independently measured with a fine particle breakage characterisation device, the JKFBC. This has effectively overcome the limitation of using a default breakage appearance function for all ores in the perfect mixing ball mill model. Since the ore-specific characteristics and the machine-related specific energy parameters are mechanistically incorporated in the size reduction model, it has the capability to predict size reduction in response to changes in the ball mill feed breakage characteristics and the operation-related specific energy.